Successional patterns of subtropical montane forest from northwestern Argentina - Carilla, Julieta; Grau, Ricardo (Bosque (Valdivia), 2017)
Subtropical montane forests from NW Argentina are characterized by a mosaic of different forest unities originated after grazing pressure reduction in different successional stages. This study analyzed successional trajectory of four forest situations, in terms of composition, structure and demography; including three secondary forest situations dominated by Alnus acuminata, Crinodendron tucumanum and Podocarpus parlatorei, and one old grow forests situation dominated by Myrtaceae family species. Ten permanent plots established at 1,700 m asl in Sierra San Javier, Tucumán, were permanently monitored in 1991 and re-measured in 1996, 2001 and 2007. Alnus acuminata and C. tucumanum secondary forests presented a fast accumulation of biomass, reaching 181 t/ha in few decades. P. parlatorei forests reached high values of biomass (393 t/ha), similar to those reached by Myrtaceae forest (418 t/ha). However, in both situations, forest biomass decreased due to the mortality of pioneer species that accumulated great amount of basal area and to the low recruitment of old growth forest species. We conclude that despite variability in change rates, secondary forest tended to converge in composition towards more diverse Myrtaceae forest with slow replacement of old growth species and high understory treelet recruitment, as Solanum grossum. These long term studies are useful to understand montane forest dynamic and their ecosystems services, such as their effect in carbon sequestration, watershed protection and regional biodiversity conservation.